Asymmetry of Grasp in Haptic Perception - Gonzalez Franco, Mar; Sinclair, Mike; Ofek, Eyal (ACM Symposium on Applied Perception 2020 (SAP '20), 2020)
In this paper we present evidence that human perception of grasp might be most dependent on the information retrieved during the inward latch rather than the release of objects. This research is motivated by a number of haptic simulations and devices and grounded in perception science. We ran a user study (n=12) with two devices one capable of delivering compliant simulations for both grip and release (CLAW), i.e. symmetric device; the other only capable of delivering adaptive grip simulations (CapstanCrunch), i.e. asymmetric device. We fund that both performed similarly well for realism scores in a grasping task with objects of different stiffness. That similar performance was despite CapstanCrunch release was delivered by a constant spring independently of the compliance of the object. Our results show preliminary evidence that when simulating haptic grasp the release might be less important. And we propose a new theory of asymmetry of grasp in haptic perception. Mar Gonzalez-Franco, Mike Sinclair, and Eyal Ofek. 2020. Asymmetry of Grasp in Haptic Perception. In ACM Symposium on Applied Perception 2020 (SAP '20), September 12–13, 2020, Virtual Event, USA. ACM, New York, NY, USA 5 Pages. https://doi.org/10.1145/3385955.3407934